Recyclable water-soluble lithium ion battery positive electrode binder, positive electrode plate adopting binder, and preparation and regeneration methods and application of positive electrode plate

By using water-soluble lithium silicate-based compounds as the positive electrode binder of lithium-ion batteries and combined with ultrasonic treatment, the problem of difficulty in removing PVDF is solved, efficient and environmentally friendly electrode components separation is achieved, and the sustainability and economicality of lithium-ion battery recycling is improved.

CN120554965APending Publication Date: 2025-08-29ZHAOQING JINSHENG METAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510701148.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

During the recycling process of existing lithium-ion batteries, the removal of the binder PVDF is difficult, the energy consumption is high, the cost is high, and the use of toxic solvents is difficult to separate the electrode components, affecting the sustainability and economicality of the recycling process.

Method used

The reversible water-soluble lithium silicate-based compound is used as the positive electrode binder to separate the electrode components in the aqueous solution by sonication. The design is simple, environmentally friendly and compatible with the existing battery recycling process.

Benefits of technology

High-performance electrode separation and regeneration is achieved, reducing recovery costs, improving the separation efficiency of electrode components, high bonding strength and excellent electrochemical stability, avoiding high-temperature treatment and the use of toxic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120554965A_ABST
    Figure CN120554965A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery electrode materials, and particularly relates to a water-soluble positive electrode binder based on a surface coating stabilization strategy, the chemical general formula of the water-soluble positive electrode binder is LixSiyOz, x is equal to 2, y is equal to 1 / 5, and z is equal to 3 / 11. The binder effectively anchors positive active particles through an interface coating effect, and inhibits structure degradation in a circulation process, so that the electrode stability is improved. Due to the water-soluble characteristic, the electrode assembly can realize efficient separation and recovery of an active substance, a current collector and a binder through a water immersion method, and the battery recovery cost is greatly reduced. The material has the characteristics of high bonding strength, low processing viscosity and environmental friendliness, and the prepared positive pole piece shows good peelability while maintaining excellent electrochemical performance, and has remarkable industrial application value in the fields of power batteries and energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium-ion battery positive electrode binder, and more specifically, to a recyclable water-soluble lithium-ion battery positive electrode binder. The present invention also relates to a positive electrode sheet using the positive electrode binder and a method for regenerating the positive electrode sheet. Background Art

[0002] Lithium-ion batteries (LIBs) have become the primary power source for electronic products, electric vehicles (EVs), and energy storage systems (ESS) due to their high energy density, long lifespan, and lack of memory effect. Currently, the lifespan of state-of-the-art LIBs is approximately 6-8 years, indicating that a large amount of waste LIBs will be generated in the near future. It is estimated that by 2030, the global capacity of scrapped LIBs will exceed 104 GWh. Efficient recycling and utilization of waste LIBs has become an urgent requirement for achieving carbon neutrality goals and developing a circular economy. On the one hand, waste LIBs contain a large amount of valuable elements, such as cobalt (Co), nickel (Ni), and lithium (Li), the extraction of which is restricted by limited natural resources and geopolitical factors. On the other hand, heavy metals in waste LIBs pose environmental toxicity issues and may accumulate in biological systems, ultimately endangering human health.

[0003] At present, the recycling of waste lithium batteries mainly involves pyrometallurgy, hydrometallurgy and direct regeneration processes, all of which face the problem of raw material separation (i.e. disassembling and separating the various components of the battery), which requires optimization from the perspective of the binder. More precisely, the binder tightly binds the electroactive particles to the conductive agent and the current collector, making them difficult to separate. For example: commercial positive electrodes usually use polyvinylidene fluoride (PVDF) as a binder, which is a highly non-reactive and hydrophobic fluoropolymer with excellent resistance to most chemicals and is inevitably difficult to eliminate or degrade. Although strategies such as heat treatment and the use of organic solvents have been proven to remove binders from recycled electrodes, the large amount of energy consumption, rising costs and the use of toxic solvents essentially undermine the sustainability and economy of the battery recycling process.

[0004] Currently, PVDF remains the main binder for positive electrodes. Despite its high stability and strong adhesion, it also makes the separation of electrode components more difficult during the recycling process. Although some advanced strategies (such as heat treatment, solvent treatment, and solution treatment) have been proven to remove binders from recycled electrodes, the following problems still exist: ① The process of removing the binder is energy-intensive, costly, and uses toxic solvents; ② The decomposition products of PVDF are harmful to the environment (such as hydrofluoric acid); ③ After treatment, there will still be PVDF or solvent residues on the surface of the active material or current collector. These problems essentially undermine the sustainability and economic viability of the battery recycling process.

[0005] Furthermore, despite successful separation of the active material and current collector, a considerable amount of PVDF residue still remains in the electroactive material. In this case, binders with better solubility in non-toxic solvents or even water show better sustainability in separation. Therefore, designing reversible binders that can separate electroactive materials in a simple and environmentally friendly manner will provide a huge opportunity to cultivate a sustainable closed-loop battery economy at the raw material level. Summary of the Invention

[0006] A reversible binder refers to a special adhesive material that can repeatedly bond and separate under specific conditions. Its core feature is that the bonding ability can be turned on or off "on demand", thereby achieving reversible bonding and separation of materials. The first object of the present invention is to provide a high-performance recyclable water-soluble lithium-ion battery positive electrode binder to solve the problems existing in the above-mentioned prior art, so that the components in the electrode can be separated and recycled more simply and efficiently, thereby reducing the battery recycling cost. The second object of the present invention is to provide a positive electrode sheet using the above-mentioned binder. The third object is to provide a method for preparing the above-mentioned positive electrode sheet. The fourth object is to provide a regeneration method for the above-mentioned positive electrode sheet. The fifth object is to provide an application of the above-mentioned positive electrode sheet in a lithium-ion battery.

[0007] To achieve the above first object, the present invention provides the following solution:

[0008] A recyclable water-soluble lithium-ion battery positive electrode binder, the binder is a lithium silicate-based compound, the chemical formula of which is Li x Si y O z , where x is 2, y is 1 or 5, and z is 3 or 11; that is, Li2SiO3 or Li2Si5O 11 .

[0009] In the above-mentioned positive electrode binder, the crystal structure of the binder is amorphous or partially crystalline, and the viscosity of its aqueous solution at 25° C. is 10 to 500 mPa·s.

[0010] In the above-mentioned positive electrode binder, the particle size D of the binder is 50 The particle size is 0.1~5μm, and the specific surface area is 5~200m 2 g -1 , the pH value of its aqueous solution is 9-12.

[0011] To achieve the above second purpose, the present invention provides the following solution: a lithium ion battery positive electrode sheet, comprising the following components in mass percentage: 70-99% positive electrode active material, 0.5-20% conductive agent and 0.5-10% positive electrode binder as described in claim 1.

[0012] In the above-mentioned positive electrode sheet, the positive electrode sheet current collector is aluminum foil or carbon-coated aluminum foil.

[0013] In the above-mentioned positive electrode sheet, the positive electrode active material is at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material or lithium-rich manganese-based material.

[0014] In the above-mentioned positive electrode sheet, the thickness of the positive electrode binder coating the positive electrode active material is 5 to 500 nm.

[0015] To achieve the third object, the present invention provides the following solution:

[0016] A method for preparing a positive electrode sheet as claimed in claim 4, comprising the following steps:

[0017] (1) The positive electrode binder, conductive agent and active material are placed in an aqueous solution and mixed evenly with a homogenizer or a stirrer to obtain a solution A; (2) Solution A is applied to the surface of the positive electrode current collector to obtain a semi-finished product B; (3) The semi-finished product B is placed in a high temperature environment of 80 to 150° C. and dried for 8 to 16 hours to obtain a positive electrode sheet.

[0018] To achieve the fourth objective, the present invention provides the following solutions:

[0019] A method for recycling an electrode sheet as claimed in claim 4, comprising the following steps:

[0020] 1) Soak the waste positive electrode sheet in deionized water for 0.5 to 5 minutes, and apply ultrasonic treatment at a frequency of 20 to 40 kHz and a power of 50 to 400 W for 30 to 300 seconds;

[0021] 2) Separate the positive electrode active material and the complete aluminum current collector.

[0022] An application of the positive electrode sheet as described above in a lithium-ion battery.

[0023] The binder designed in the present invention can not only improve the structural stability and electrochemical performance of the positive electrode, but also effectively solve the problem of difficulty in separating the electrode components during the recycling process, further expanding the application of the binder design in lithium battery recycling.

[0024] The present invention utilizes the design of a reversible binder to achieve a simple, efficient and environmentally friendly electrode separation and regeneration process route, which does not require high-temperature treatment or special equipment and is compatible with existing battery recycling processes.

[0025] The present invention discloses the following technical effects:

[0026] The adhesive designed by the present invention has high bonding strength and a wide electrochemical stability window.

[0027] The electrochemical performance of the binder designed in the present invention is significantly better than that of PVDF binder.

[0028] The electrodes prepared with the reversible binder designed in the present invention can be efficiently recycled in aqueous solution by a simple method; compared with electrodes prepared with PVDF binder, the recycling performance is excellent.

[0029] The present invention aims to construct an easily elutable and separable positive electrode sheet by designing a high-performance reversible binder, thereby improving the recovery efficiency of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 is the structural formula of polylithium silicate (Poly LS);

[0032] Figure 2 TEM images, (a) LRM@Poly LS electrode powder, (b) LRM particles;

[0033] Figure 3 (a) LSV test results of Poly LS adhesive, (b) peel test results of LRM@PVDF and LRM@Poly LS;

[0034] Figure 4 (a) at 1C (250mA hg -1 ) Comparison of the cycling performance of LRM@Poly LS and LRM@PVDF electrodes under (a) and (b) the corresponding discharge mid-voltage decay;

[0035] Figure 5 The cycling performance of LRM@Poly LS at 2.0~4.7V, 2C CC-CV to 0.2C;

[0036] Figure 6 Cycling performance of LRM@Poly LS-95% and LRM@PVDF-95% at 1C (a) and 1C / 2D (b);

[0037] Figure 7 Cycling performance of LRM@Poly LS-95% / / G@PVDF full battery;

[0038] Figure 8Variable scan rate CV curves of LRM@PVDF (a) and LRM@Poly LS (b), (c) calculated results of lithium ion diffusion coefficient;

[0039] Figure 9 Elution test results of LRM@Poly LS and LRM@PVDF recovery electrodes; DETAILED DESCRIPTION

[0040] The present invention provides a recyclable water-soluble lithium ion battery positive electrode binder, wherein the binder is a lithium silicate-based compound, and its general chemical formula is Li x Si y O z , where x is 2, y is 1 or 5, and z is 3 or 11; that is, lithium silicate (Li2SiO3) or lithium polysilicate (Li2Si5O 11 ).

[0041] Preferably, the crystal structure of the binder is amorphous or partially crystalline, and the viscosity of its aqueous solution at 25° C. is 10 to 500 mPa·s.

[0042] More preferably, the particle size D of the binder is 50 The particle size is 0.1~5μm, and the specific surface area is 5~200m 2 g -1 , the pH value of its aqueous solution is 9-12.

[0043] The present invention provides a lithium-ion battery positive electrode sheet comprising the following components by mass percentage: 70-99% positive electrode active material, 0.5-20% conductive agent, and 0.5-10% positive electrode binder as claimed in claim 1. The positive electrode sheet current collector is preferably aluminum foil or carbon-coated aluminum foil.

[0044] Preferably, the positive electrode active material is at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material or lithium-rich manganese-based material.

[0045] More preferably, the thickness of the positive electrode binder coating the positive electrode active material is 5 to 500 nm.

[0046] The present invention provides a method for preparing the positive electrode sheet as described above, comprising the following steps:

[0047] (1) The positive electrode binder, conductive agent and active material are placed in an aqueous solution and mixed uniformly with a homogenizer or a stirrer to obtain a solution A;

[0048] (2) Solution A is applied to the surface of the positive electrode current collector to obtain a semi-finished product B; (3) Semi-finished product B is placed in a high temperature environment of 80-150°C and dried for 8-16 hours to obtain a positive electrode. The high temperature drying (80-150°C, 8-16 hours) dehydrates and solidifies the binder, thereby achieving the bonding function.

[0049] The present invention provides a method for recycling and regenerating the positive electrode sheet as described above, comprising the following steps:

[0050] 1) Soak the waste positive electrode sheet in deionized water for 0.5 to 5 minutes, and apply ultrasonic treatment at a frequency of 20 to 40 kHz and a power of 50 to 400 W for 30 to 300 seconds;

[0051] 2) Separate the positive electrode active material and the complete aluminum current collector.

[0052] The present invention provides an application of the above-mentioned positive electrode sheet in a lithium-ion battery.

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.

[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0058] The lithium-rich manganese-based positive electrode particles (Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, LRM) and graphite (G) particles were purchased from Songhu Shenjian Technology (Dongguan) Co., Ltd. Aqueous carbon nanotube slurry (solid content 1 wt%) and oily carbon nanotube slurry (solid content 5 wt%) were purchased from Dongguan Kelude Innovation Technology Co., Ltd. Conductive carbon fiber (VGCF-H) and conductive carbon black (Super P Li) were purchased from Shenzhen Dongxia Times Technology Co., Ltd. Polylithium silicate (Poly LS, 20 wt%), lithium silicate (LS, 21 wt%), polyvinylidene fluoride (PVDF, HSV900), and N-methylpyrrolidone (NMP, ≥99.9%) were purchased from Adamas, Anaiji Chemical, Shenzhen Kejing, and Aladdin, respectively.

[0059] Example 1

[0060] Preparation of positive electrode:

[0061] (1) 0.7 g of LRM particles, 0.15 g of VGCF-H, and 0.05 g of conductive carbon black were placed in a mortar and ground to obtain a mixture 1.

[0062] (2) 0.5 g of lithium polysilicate (Poly LS, 20 wt%) and 0.7 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred to obtain solution 1.

[0063] (3) Solution 1 was spread on aluminum foil, and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@Poly LS-70%).

[0064] Example 2

[0065] Preparation of positive electrode:

[0066] (1) 0.8 g of LRM particles and 0.1 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0067] (2) 0.5 g of lithium polysilicate (Poly LS, 20 wt%) and 0.7 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred to obtain solution 1.

[0068] (3) Solution 1 was scraped onto aluminum foil and dried in a vacuum oven at 120°C for 8-12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@Poly LS).

[0069] Example 3

[0070] Preparation of positive electrode:

[0071] (1) 0.9 g of LRM particles and 0.05 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0072] (2) 0.25 g of lithium polysilicate (Poly LS, 20 wt%) and 0.6 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred to obtain solution 1.

[0073] (3) Solution 1 was spread on aluminum foil, and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@Poly LS-90%).

[0074] Example 4

[0075] Preparation of positive electrode:

[0076] (1) 0.95 g of LRM particles and 0.03 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0077] (2) 0.1 g of lithium polysilicate (Poly LS, 20 wt%) and 0.6 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred to obtain solution 1.

[0078] (3) Solution 1 was spread on aluminum foil, and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@Poly LS-95%).

[0079] Example 5

[0080] Preparation of positive electrode:

[0081] (1) 0.99 g of LRM particles and 0.005 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0082] (2) 0.025 g of lithium polysilicate (Poly LS, 20 wt%) and 0.6 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred to obtain solution 1.

[0083] (3) Solution 1 was spread on aluminum foil and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@Poly LS-99%).

[0084] Example 6

[0085] Preparation of positive electrode:

[0086] (1) 0.8 g of LRM particles and 0.1 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0087] (2) 0.476 g of lithium silicate (21 wt%) and 0.7 g of aqueous carbon nanotube slurry (1 wt%) were added to mixture 1, and then an appropriate amount of water was added and stirred uniformly to obtain solution 1.

[0088] (3) Solution 1 was spread on aluminum foil and dried in a vacuum oven at 120°C for 8-12 hours. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@LS).

[0089] Example 7

[0090] Preparation of negative electrode sheet:

[0091] (1) 0.9 g of graphite particles and 0.05 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0092] (2) 0.05 g of polyvinylidene fluoride (PVDF) and 0.06 g of oil-based carbon nanotube slurry (5 wt%) were added to mixture 1, and then an appropriate amount of N-methylpyrrolidone was added and stirred uniformly to obtain solution 1.

[0093] (3) Solution 1 was scraped onto a copper foil and dried in a vacuum oven at 80°C for 8-12 hours. After cooling naturally, the solution was taken out for use to obtain an electrode sheet (named G@PVDF).

[0094] Example 8

[0095] Reference for electrode recycling method:

[0096] (1) Immerse the electrode to be recycled in deionized water for 1 minute until it is completely wetted.

[0097] (2) Ultrasonic treatment was applied at a frequency of 40 kHz and a power of 400 W for 60 s.

[0098] (3) Filtration and separation to obtain "black powder" (containing active substances) and complete aluminum current collector. Separation efficiency is as follows Figure 9 shown.

[0099] Comparative Example 1

[0100] Preparation of positive electrode:

[0101] (1) 0.7 g of LRM particles, 0.15 g of VGCF-H, and 0.05 g of conductive carbon black were placed in a mortar and ground to obtain a mixture 1.

[0102] (2) 0.1 g of PVDF and 0.07 g of oily carbon nanotube slurry (5 wt%) were added to the mixture 1, and then an appropriate amount of water was added and stirred uniformly to obtain a solution 1.

[0103] (3) Solution 1 was spread on aluminum foil and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@PVDF-70%).

[0104] Comparative Example 2

[0105] Preparation of positive electrode:

[0106] (1) 0.8 g of LRM particles and 0.1 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0107] (2) 0.1 g of polyvinylidene fluoride (PVDF) and 0.07 g of oily carbon nanotubes (5 wt%) were added to mixture 1, and then an appropriate amount of N-methylpyrrolidone was added and stirred uniformly to obtain solution 1.

[0108] (3) Solution 1 was scraped onto aluminum foil and dried in a vacuum oven at 120°C for 8-12 h. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@PVDF).

[0109] Comparative Example 3

[0110] Preparation of positive electrode:

[0111] (1) 0.9 g of LRM particles and 0.05 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0112] (2) 0.05 g of polyvinylidene fluoride (PVDF) and 0.06 g of oily carbon nanotubes (5 wt%) were added to mixture 1, and then an appropriate amount of N-methylpyrrolidone was added and stirred uniformly to obtain solution 1.

[0113] (3) Solution 1 was scraped onto aluminum foil and dried in a vacuum oven at 120° C. for 8 to 12 h. After cooling naturally, the foil was taken out for later use to obtain an electrode sheet (named LRM@PVDF-90%).

[0114] Comparative Example 4

[0115] Preparation of positive electrode:

[0116] (1) 0.95 g of LRM particles and 0.03 g of conductive carbon black were placed in a mortar and ground to obtain a mixture of 1

[0117] (2) 0.02 g of polyvinylidene fluoride (PVDF) and 0.06 g of oily carbon nanotubes (5 wt%) were added to mixture 1, and then an appropriate amount of N-methylpyrrolidone was added and stirred to obtain solution 1.

[0118] (3) Solution 1 was spread on aluminum foil and dried in a vacuum oven at 120°C for 8-12 hours. After cooling naturally, the foil was taken out for use to obtain an electrode sheet (named LRM@PVDF-95%).

[0119] Experimental example

[0120] Table 1 Comparison of electrochemical properties of electrodes prepared with different binders

[0121]

[0122] As can be seen from Table 1, the electrochemical performance of the electrode prepared with the binder of the present invention is much better than that of the electrode prepared with the existing PVDF binder.

[0123] The electrode materials prepared in Examples 1-3 of the present invention were characterized:

[0124] (1) Material characterization:

[0125] The electrode materials were characterized by transmission electron microscopy (TEM).

[0126] (2) Electrochemical performance characterization:

[0127] The prepared electrode sheet was cut into Φ = 12mm discs and placed in an argon-filled glove box (H2O < 0.1ppm, O2 < 0.1ppm). A button cell was assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet (counter electrode), separator, electrode sheet, and positive electrode shell. The electrolyte was 1M LiPF6 in EC:DMC = 3:7, and then packaged to obtain a CR2025 button cell. The battery was subjected to constant current charge and discharge tests using a Blue Power battery tester. Unless otherwise specified, the test voltage range was 2.0-4.8V and the test rate was 1C = 250mAh g. -1 .

[0128] Figure 1 It is the structural formula of polylithium silicate (Poly LS).

[0129] Figure 2 TEM images, (a) LRM@Poly LS electrode powder, (b) LRM particles. Figure 1It can be seen that a uniform and dense Poly LS coating layer is formed on the LRM surface, which is also confirmed by the distribution of Si in the Mapping results.

[0130] Figure 3 (a) LSV test results of Poly LS adhesive, (b) peel test results of LRM@PVDF and LRM@Poly LS. Figure 2 As can be seen in a, Poly LS binder has excellent electrochemical stability in the range of 2.5 to 5.5 V; Figure 2 As can be seen in b, the bonding strength of Poly LS adhesive (21.65 N m -1 ) is significantly better than PVDF binder (5.28N m -1 ).

[0131] Figure 4 (a) at 1C (250 mAh g -1 (a) Comparison of the cycling performance of LRM@Poly LS and LRM@PVDF electrodes under different cycling conditions, and (b) the corresponding voltage decay during discharge. The figure shows that the Poly LS binder not only improves the cycling performance of the LRM electrode but also effectively suppresses voltage decay during cycling.

[0132] Figure 5 The cycling performance of LRM@Poly LS at 2.0~4.7V, 2C CC-CV to 0.2C (2C constant current charge to 4.8V, and then constant voltage charge to 0.2C).

[0133] Figure 6 Cycling performance of LRM@Poly LS-95% and LRM@PVDF-95% at 1C (a) and 1C / 2D (1C charge, 2C discharge) (b).

[0134] Figure 7 Cycling performance of LRM@Poly LS-95% / / G@PVDF full battery.

[0135] Figure 8 In the figure, the variable scan rate CV curves of LRM@PVDF (a) and LRM@Poly LS (b), and (c) the calculated results of the lithium ion diffusion coefficient. It can be seen from the figure that the lithium ion diffusion coefficient of the LRM@Poly LS electrode is better than that of the LRM@PVDF electrode.

[0136] Figure 9 The elution test results of LRM@Poly LS and LRM@PVDF recovery electrodes are shown in the figure. As can be seen from the figure, the average stripping rate of LRM@Poly LS in aqueous solution is as high as 98%, while the LRM@PVDF electrode cannot be stripped in aqueous solution.

[0137] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A recyclable water-soluble lithium ion battery positive electrode binder, characterized in that: The binder is a lithium silicate-based compound, and its chemical formula is Li x Si y O z , where x is 2, y is 1 or 5, and z is 3 or 11; that is, Li2SiO3 or Li2Si5O 11 .

2. The positive electrode binder according to claim 1, characterized in that The crystal structure of the binder is amorphous or partially crystalline, and the viscosity of its aqueous solution at 25° C. is 10 to 500 mPa·s.

3. The positive electrode binder according to claim 1, characterized in that The particle size D of the binder 50 The particle size is 0.1~5μm, and the specific surface area is 5~200m 2 g -1 , the pH value of its aqueous solution is 9-12.

4. A lithium-ion battery positive electrode sheet, characterized in that: The invention comprises the following components in percentage by mass: 70-99% of positive electrode active material, 0.5-20% of conductive agent and 0.5-10% of positive electrode binder as claimed in claim 1.

5. The positive electrode sheet according to claim 4, characterized in that: The positive electrode current collector is aluminum foil or carbon-coated aluminum foil.

6. The positive electrode sheet according to claim 4, characterized in that: The positive electrode active material is at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material or lithium-rich manganese-based material.

7. The positive electrode sheet according to claim 4, characterized in that: The thickness of the positive electrode binder coating the positive electrode active material is 5 to 500 nm.

8. A method for preparing a positive electrode sheet as claimed in claim 4, characterized in that: The steps include: (1) The positive electrode binder, conductive agent and active material are placed in an aqueous solution and mixed evenly with a homogenizer or a stirrer to obtain a solution A; (2) Solution A is applied to the surface of the positive electrode current collector to obtain a semi-finished product B; (3) The semi-finished product B is placed in a high temperature environment of 80 to 150° C. and dried for 8 to 16 hours to obtain a positive electrode sheet.

9. A method for recycling a positive electrode sheet as claimed in claim 4, characterized in that: The steps include: 1) Soak the waste positive electrode sheet in deionized water for 0.5 to 5 minutes, and apply ultrasonic treatment at a frequency of 20 to 40 kHz and a power of 50 to 400 W for 30 to 300 seconds; 2) Separate the positive electrode active material and the complete aluminum current collector.

10. Use of the positive electrode sheet according to claim 4 or 9 in a lithium ion battery.